Beginning Arduino - McRoberts, Michael; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2013)
Want to light up a display? Control a touch screen? Program a robot? The Arduino is a microcontroller board that can help you do all of these things, plus nearly anything you can dream up. Even better, it's inexpensive and, with the help of Beginning Arduino, Second Edition, easy to learn. In Beginning Arduino, Second Edition, you will learn all about the popular Arduino by working your way through a set of 50 cool projects. You'll progress from a complete Arduino beginner to intermediate Arduino and electronic skills and the confidence to create your own amazing projects. You'll also learn about the newest Arduino boards like the Uno and the Leonardo along the way. Absolutely no experience in programming or electronics required! Each project is designed to build upon the knowledge learned in earlier projects and to further your knowledge of Arduino programming and electronics. By the end of the book you will be able to create your own projects confidently and with creativity. You'll learn about: Controlling LEDs Displaying text and graphics on LCD displays Making a line-following robot Using digital pressure sensors Reading and writing data to SD cards Connecting your Arduino to the Internet This book is for electronics enthusiasts who are new to the Arduino as well as artists and hobbyists who want to learn this very popular platform for physical computing and electronic art.   Please note: The print version of this title is black and white; the eBook is full color. The color fritzing diagrams are available in the source code downloads on http://www.apress.com/9781430250166 .
Keywords: Computer input-output equipment; Computer hardware; Hardware and Maker; Computer Hardware